Indexes of skin activity and damage in patients with systemic lupus erythematosus – CLASI and R-CLASI - А. А. Shumilova; F. A. Cheldieva; К. S. Nurbaeva; Е. I. Travkiva; Т. М. Reshetnyak (Научно-практическая ревматология)
Introduction. Cutaneous Lupus Disease Area and Severity Index (CLASI) and its modified version, the Revised Cutaneous Lupus Erythematosus Disease Areas and Severity Index (R-CLASI) are tools for quantifying skin and mucosal lesions in patients with both cutaneous lupus erythematosus and its systemic variant. Evaluation of the scales of activity and skin damage in systemic lupus erythematosus (SLE) is associated with the need to stratify their quantitative characteristics. The Cutaneous Lupus Disease Area and Severity Index (CLASI) and its modified version the Revised Cutaneous Lupus Erythematosus Disease Area and Severity Index (R-CLASI) are a tool for quantifying skin and mucosal lesions in patients with both cutaneous lupus erythematosus (CLE) and its system version.Objective. To validate the indexes of objective assessment of skin activity and damage CLASI and R-CLASI in the Russian cohort of patients with systemic lupus erythematosus and compare it with dermatological assessments of the quality of life.Material and methods. The study included 55 patients with SLE with various types of skin and mucosal lesions, the median age was 30.0 [26.0; 40.0] years, the duration of the disease was 7.0 [3.0; 14.0] years. To assess the active (reversible) lesion and irreversible skin damage, the CLASI and R-CLASI indexes were used, for the general assessment of activity and damage in SLE, the SLEDAI-2K and SLICC/ACR DI were used.Results. The most common variant of skin lesions in patients with SLE is acute cutaneous lupus erythematosus (ACLE) – 45%, as well as alopecia, which occurs in 62% of cases. The median activity index for CLASI was 5.0 [2.0; 11.0], and R-CLASI was 7.0 [3.0; 18.0]; the median damage index for CLASI was 5.0 [2.0; 11.0], and R-CLASI was 2.0 [0.0; 7.0]. A significant relationship was revealed between the medians of CLASI and R-CLASI scores depending on the degree of activity according to SLEDAI-2K (Systemic Lupus Erythematosus Disease Activity Index) and the damage Index (DI) in SLE (SLICC/ACR DI, Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index) when recalculating these indexes only for skin and mucous lesions. According to the ROC analysis, the CLASI and R-CLASI skin activity and damage indices showed high sensitivity (CLASI activity index – 98%, R-CLASI – 93%, CLASI and R-CLASI damage index – 91%) and specificity (CLASI activity index – 64%, R-CLASI – 71%, CLASI and R-CLASI damage index – 86%).Conclusion. To assess the severity of skin and mucosal lesions in patients with SLE in the Russian Federation, it is reasonable to use the CLASI and R-CLASI indices. The CLASI and R-CLASI indices reflect the level of activity and severity of skin lesions, with higher values of these indices indicating more severe skin lesions and a significant impact on the overall well-being of SLE patients. Patients with high values of these indices often experience feelings of embarrassment, discomfort, difficulty in performing daily tasks, and limitations in social life. To assess the severity of skin and mucous lesions in patients with SLE in the Russian Federation, it is advisable to use the CLASI and R-CLASI indexes.